Method for detecting fatigue performance of asphalt pavement

By simulating the interlayer damage state between the asphalt concrete surface layer and the base layer and conducting fatigue test detection methods, the insufficient research problem of the impact of pavement life in the existing technology is solved, and high-accuracy detection of asphalt road fatigue performance is achieved and estimates.

CN119437950AInactive Publication Date: 2025-02-14CHINA MCC22 GROUP CORP LTD +1

Patent Information

Application Number
CN202510019060.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The lack of research on the impact of the contact state between the asphalt concrete surface layer and the base layer on the pavement life is achieved in the prior art, which makes it impossible to comprehensively evaluate the fatigue performance of asphalt pavement.

Method used

A detection method is adopted to simulate the composite trabecula of actual road surface damage, and to simulate the interlayer damage state between the asphalt surface layer and the cement-stabilized gravel layer by using the interlayer barrier method. Fatigue tests are carried out to study the interlayer state on the asphalt road surface. Effects of fatigue performance.

Benefits of technology

By simulating the actual interlayer damage of the road surface, the impact of the interlayer state on the fatigue performance of asphalt pavement can be studied with high accuracy, thereby estimating the impact of the degree of interlayer damage on the fatigue life of the road surface, and making the asphalt pavement Design and construction provide rational suggestions and theoretical basis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119437950A_ABST
    Figure CN119437950A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of road engineering, and particularly relates to a method for detecting the fatigue performance of an asphalt pavement, which comprises the following steps: firstly, manufacturing a composite small beam for detection: manufacturing a water-stable layer by using a concrete material; then a blocking agent is applied to the top face of the water-stable layer, so that bonding between the asphalt surface layer and the water-stable layer is blocked, the effect that interlayer thorough disengaging and bonding failure are achieved, and interlayer damage is simulated; paving an asphalt surface layer on the top surface of the cement-stabilized layer and compacting to form a test composite board, and cutting the test composite board to form a composite small beam; and putting the composite small beam into a fatigue testing machine, and repeating the loading times to obtain the fatigue life of the composite small beam. According to the scheme, a method for researching the influence of the interlayer state on the fatigue performance of the asphalt pavement is provided, and corresponding rationalized suggestions and theoretical bases can be provided for design and construction of the asphalt pavement based on the analysis; according to the method, the interlayer damage of the actual asphalt pavement is simulated, so that the detection accuracy is very high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of highway engineering, and in particular relates to a method for detecting fatigue performance of an asphalt pavement. Background Art

[0002] In recent years, the traffic volume has been increasing day by day. Many asphalt pavements in my country have cracked to varying degrees under the influence of load and natural environment. There are many methods for fatigue testing of asphalt mixtures. Commonly used detection methods are: one is to use a single-layer asphalt concrete beam as the research object, that is, only the asphalt concrete structure of the pavement is used to predict the life of the pavement; the second is to obtain the mechanical parameters of each structural layer of the asphalt pavement, simulate the corresponding parameters through indoor molding specimens, and analyze the influence of each layer parameter on the fatigue performance of the asphalt pavement.

[0003] In recent years, many scholars at home and abroad have conducted research on cracks and found that at the cracks in the pavement, the connection between the asphalt surface layer and the base layer has different degrees of damage. Therefore, if you want to comprehensively evaluate the fatigue performance of asphalt pavements, you need to test the fatigue performance of asphalt pavements under different interlayer damage conditions. Many studies have shown that the interlayer performance is constantly damaged and deteriorated during the service of the road, and the fatigue performance of asphalt pavements is indeed affected by the interlayer state. However, there are insufficient means to detect the specific impact and the relationship between the interlayer damage state and the performance of asphalt pavements. Therefore, it is necessary to propose a test method for fatigue performance of asphalt pavements that takes into account the interlayer state. Summary of the invention

[0004] The present invention aims to solve the problem that in the prior art, there is a lack of research on the impact of the contact state between the asphalt concrete surface layer and the base layer on the life of the asphalt pavement, and thus proposes a means of detecting the relationship between the fatigue performance of the asphalt pavement and the influence of the interlayer state.

[0005] The present invention solves the above-mentioned problem by adopting the following technical solution: A method for testing fatigue performance of asphalt pavement is carried out according to the following steps: The first step is to make a composite beam for testing: 1) According to the common raw material ratio of the road surface water-stabilizing layer, the cement-stabilized gravel layer is made through the first mold and maintained; 2) After the cement-stabilized crushed stone layer is taken out from the first mold, a barrier agent is applied to its top surface to simulate interlayer damage, and after the barrier agent is cured, the cement-stabilized crushed stone layer is converted into a base plate; 3) placing the substrate into the second mold, spreading the binder on the area other than the portion on the top surface of the substrate where the barrier agent is applied, spreading the asphalt surface layer on the substrate and compacting it to form a test composite board; 4) After curing the test composite board, cut the test composite board into long strip composite beams; The second step is to conduct fatigue test: 5) Place the composite beam into a fatigue testing machine, set the temperature, load size, load frequency and load application form, and apply repeated loads to the composite beam through the repeated loading fatigue testing machine until the composite beam is fatigue-damaged; 6) The final number of repeated loading is the fatigue life of the composite beam, and the size of the fatigue life reflects the fatigue performance of the composite beam.

[0006] Compared with the prior art, the present invention adopting the above structure has the following beneficial effects: This scheme provides a method for testing the fatigue performance of asphalt pavement. A composite small beam is made to simulate the interlayer damage of the actual pavement. During the production process, the interlayer barrier method is used to simulate the interlayer damage state of the asphalt surface layer and the cement-stabilized gravel layer. The corresponding fatigue test is carried out based on the composite small beam to study the influence of the interlayer state on the fatigue performance of the asphalt pavement, and then the influence of the degree of interlayer damage on the fatigue life of the pavement is estimated. Based on this analysis, corresponding reasonable suggestions and theoretical basis can be provided for the design and construction of asphalt pavements. Since this method simulates the damage between the actual asphalt pavement layers, the detection accuracy is very high.

[0007] As a preferred embodiment, a further technical solution of the above structure is: The first mold is a rutting plate test mold with a length of 300mm, a width of 300mm, and a height of 50mm; the second mold is a rutting plate test mold with a length of 300mm, a width of 300mm, and a height of 100mm. The thickness of the asphalt mixture spread on the base plate is 20mm to 25mm.

[0008] The composite beam is 300mm long, 100mm wide and 75mm thick, containing a 50mm thick cement-stabilized gravel layer and a 25mm thick asphalt surface layer.

[0009] There are several types of layouts for the application range of the barrier agent. The test composite panels with different application ranges of the barrier agent are divided into three groups of samples, namely: Group A: Sample A201 has an interlayer barrier of 0%, sample A202 has an interlayer barrier of 25%, sample A203 has an interlayer barrier of 50%, sample A204 has an interlayer barrier of 75%, and sample A205 has an interlayer barrier of 100%; Group B: The centroid distance between the damaged parts of the layers of sample B201 is 37.5mm; the centroid distance between the damaged parts of the layers of sample B202 is 46.9mm; the centroid distance between the damaged parts of the layers of sample B203 is 56.25; the centroid distance between the damaged parts of the layers of sample B204 is 65.63mm; the centroid distance between the damaged parts of the layers of sample B205 is 75mm; Group C: The interlayer friction coefficient of sample C201 is 0.4, the interlayer friction coefficient of sample C202 is 0.5, the interlayer friction coefficient of sample C203 is 0.6, the interlayer friction coefficient of sample C204 is 0.7, and the interlayer friction coefficient of sample C205 is 0.8.

[0010] Optionally, the barrier agent is a high temperature resistant smooth paint. Optionally, the binder is emulsified asphalt.

[0011] Step 5) Medium load application method: set two left-right symmetrical support points at the bottom of the composite beam, and apply pressure to the midpoint of the top surface of the composite beam. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 : is a flow chart of the fatigue performance detection method of asphalt concrete pavement structure of the present invention; Figure 2 :It is the first mold diagram of the present invention; Figure 3 :It is the second mold diagram of the present invention; Figure 4 : It is the test composite board diagram; Figure 5 : Examples of samples simulating different interlayer damage area ratios according to the present invention; Figure 6 : This is an example of a sample simulating the centroid distance of different interlayer damage parts in the present invention; Figure 7 : It is an example of a sample for simulating the bonding condition of different interlayer damage parts of the present invention; Figure 8 : Example of road damage; Fig. 9 : Schematic diagram of cutting the test composite board of the present invention into composite beams.

[0013] Explanation of the accompanying drawings: 1. First mold; 2. Second mold; 3. Cement-stabilized gravel layer; 4. Barrier; 5. Asphalt surface layer; 6. Binder. DETAILED DESCRIPTION

[0014] The present invention will be further described below in conjunction with embodiments, the purpose of which is only to provide a better understanding of the content of the present invention. Therefore, the examples given do not limit the protection scope of the present invention.

[0015] See also Figure 1 The asphalt pavement fatigue performance detection method provided by the present invention is The first step is to make a composite beam for testing: 1) According to the common raw material ratio of the road surface water-stabilizing layer, the cement-stabilized crushed stone layer 3 is manufactured by the first mold 1 and maintained.

[0016] See also Figure 2The first mold 1 is a rutting plate test mold with a specification of 300mm long × 300mm wide × 50mm high, which is a steel structure template; when making the cement stabilized gravel layer 3, the required raw material value is calculated according to the volume of the cement stabilized gravel layer 3 structure to be tested, and the concrete material production of the cement stabilized gravel layer 3 needs to maintain the uniformity of the mixture.

[0017] 2) After the cement-stabilized gravel layer 3 is taken out from the first mold 1, a barrier agent 4 is applied to its top surface. The application range of the barrier agent 4 can be set to several different arrangement types to simulate different degrees of damage between layers. After the barrier agent 4 is cured, the cement-stabilized gravel layer 3 is converted into a substrate.

[0018] The barrier agent 4 may be a high temperature resistant smooth paint, which can block the bonding between the asphalt surface layer 5 and the cement stabilized gravel layer 3, achieving the effect of complete interlayer debonding failure. The present invention uses this method to simulate interlayer damage. The range of applying the barrier agent 4 is the range set for interlayer damage, and the present invention introduces three descriptive parameters of the interlayer state.

[0019] (1) Interlayer damage area ratio: the ratio of the interlayer damage area to the overall interlayer bonding area. The interlayer damage area ratio is used to describe the interlayer damage area of ​​pavement under different conditions. By setting different interlayer damage area ratios, the influence of different interlayer damage area sizes on pavement fatigue performance can be studied. Optional, see Figure 4 and Figure 5 In the embodiment shown, a group A of samples are used to detect the influence of the interlayer damage area ratio on fatigue life. The interlayer barrier areas are all located on the center line of the substrate, and the interlayer damage area ratios are set to sample A201: 0%; sample A202: 25%; sample A203: 50%; sample A204: 75%; and sample A205: 100%.

[0020] (2) Interlayer damage location centroid distance: The distance between the interlayer damage location centroid and the load centroid. The interlayer damage location centroid distance is used to describe the position of the interlayer damage location of the pavement under different conditions. By setting different interlayer damage location centroid distances, the influence of interlayer damage at different positions on the fatigue performance of the pavement can be studied. For example, the embodiment provided in this scheme is used to detect the influence of the interlayer damage centroid distance on the fatigue life of the pavement in Group B samples, see Figure 6 , Figure 8 The example given is based on sample A202 (interlayer damage area ratio is 25%), and different centroid distances are set respectively: the centroid distance of the interlayer damage part of sample B201 is 37.5mm; the centroid distance of the interlayer damage part of sample B202 is 46.9mm; the centroid distance of the interlayer damage part of sample B203 is 56.25; the centroid distance of the interlayer damage part of sample B204 is 65.63mm; the centroid distance of the interlayer damage part of sample B205 is 75mm.

[0021] (3) Bonding condition of interlayer damaged parts: The bonding degree of interlayer damaged parts. The bonding condition of interlayer damaged parts is used to describe the connection and damage degree of interlayer damaged parts of pavement in different conditions. By setting different bonding conditions of interlayer damaged parts, the influence of different interlayer damage degrees on pavement fatigue performance can be studied. The present invention simulates different bonding strengths by spreading different doses of adhesive in advance on the bonding part between the asphalt surface layer 5 and the cement stabilized crushed stone layer 3. Figure 7 In the embodiment shown, based on sample B205, the bonding conditions of different damaged parts are: the interlayer friction coefficient of sample C201 is 0.4, the interlayer friction coefficient of sample C202 is 0.5, the interlayer friction coefficient of sample C203 is 0.6, the interlayer friction coefficient of sample C204 is 0.7, and the interlayer friction coefficient of sample C205 is 0.8. The binder can be emulsified asphalt. Through the shear test, the corresponding relationship between different friction coefficients and binder dosages is calculated, and different friction coefficient control groups are reasonably set.

[0022] In the test, the three parameters are arbitrarily combined and as many samples as possible are prefabricated to ensure the accuracy of the results. According to the parameters of each sample designed in the test plan, interlayer barrier measures are applied to the top surface of the substrate corresponding to the set damage location.

[0023] 3) Place the substrate into the second mold 2, first check whether the surface of the barrier agent 4 is completely dry and smooth, then spread the adhesive 6 on the area other than the portion of the top plate of the substrate where the barrier agent 4 is applied, and then spread the asphalt surface layer 5 on the substrate and compact it to form a test composite board.

[0024] See also Figure 3 The second mold 2 is a rutting plate test mold with a size of 300mm×300mm×100mm (length×width×height). The rutting plate is firmly installed and the base plate is placed with the paint surface facing up. The asphalt mixture of the asphalt surface layer 5 should be made of ingredients that meet the test mix design. Its paving and rolling temperature should strictly meet the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering". The asphalt mixture is then rolled and formed using a wheel roller. The rolling speed, frequency, temperature, pressure and other parameters strictly meet the requirements of the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".

[0025] 4) After curing the test composite board, cut the test composite board into long strip-shaped composite beams.

[0026] After the asphalt surface layer 5 is formed, it needs to be placed for 24 hours to cool down; then the second mold 2 is disassembled, and the composite board is cut into composite beams by a cutting machine in a direction perpendicular to the barrier 4, such as Fig. 9As shown, in this example, the composite beam is 300 mm long, 100 mm wide and 75 mm thick (including a 50 mm thick cement stabilized gravel layer and a 25 mm thick asphalt surface layer, the adhesive 6 is a permeable material and its thickness is not recorded, and the barrier 4 is too thin to be recorded).

[0027] The second step is to conduct fatigue test: 5) Place the composite beam into a fatigue testing machine, repeatedly load the fatigue testing machine, set parameters such as temperature, load size, load frequency, and load application form, and apply repeated loads to the composite beam until fatigue failure occurs.

[0028] 6) The number of repeated loadings finally obtained is the fatigue life of the composite beam, and the size of the fatigue life reflects the fatigue performance of the composite beam. The fatigue life data of all composite beams are recorded, and the influence of interlayer damage on the actual fatigue performance of the road is obtained through analysis.

[0029] Specifically, the load application method is as follows: two support points are symmetrically arranged at the bottom of the composite beam, and pressure is applied to the midpoint of the top surface of the composite beam.

[0030] Compared with the prior art: the method for detecting fatigue performance of asphalt pavement provided by the present invention includes simulating interlayer damage between the road asphalt surface layer 5 and the cement stabilized gravel layer 3 by using an interlayer barrier method, making composite beams with different levels of interlayer damage, and conducting corresponding fatigue tests based on the composite beams, so as to study the influence of interlayer state on fatigue performance of asphalt pavement, and then estimate the influence of interlayer damage degree on pavement fatigue life. Based on this analysis, corresponding rationalization suggestions and theoretical basis can be provided for the design and construction of asphalt pavement. Since the method for detecting fatigue performance of asphalt pavement is to simulate the damage between actual asphalt pavement layers, the detection accuracy is very high.

[0031] The above description is only a preferred feasible embodiment of the present invention, and does not limit the scope of rights of the present invention. All equivalent changes made using the contents of the present specification and its drawings are included in the scope of rights of the present invention.

Claims

1. A method for detecting fatigue performance of asphalt pavement, characterized in that: The first step is to make a composite beam for testing: 1) According to the commonly used raw material ratio of the road surface water-stabilizing layer, a cement-stabilized crushed stone layer (3) is produced by a first mold (1) and then maintained; 2) After the cement-stabilized crushed stone layer (3) is taken out from the first mold (1), a barrier agent (4) is applied to the top surface thereof to simulate interlayer damage, and after the barrier agent (4) is cured, the cement-stabilized crushed stone layer (3) is converted into a base plate; 3) placing the substrate into the second mold (2), spreading the binder (6) on the area of ​​the top surface of the substrate other than the portion where the barrier agent (4) is applied, and then spreading the asphalt surface layer (5) on the substrate and compacting it to form a test composite board; 4) After the test composite board is cured, the test composite board is cut into long strips of composite beams; The second step is to conduct fatigue test: 5) Place the composite beam into a fatigue testing machine, set the temperature, load size, load frequency and load application form, and apply repeated loads to the composite beam through the repeated loading fatigue testing machine until the composite beam is fatigue-damaged; 6) The number of repeated loadings finally obtained is recorded as the fatigue life of the composite beam. The size of the fatigue life reflects the fatigue performance of the composite beam.

2. The method for detecting fatigue performance of asphalt pavement according to claim 1, characterized in that: The first mold (1) is a rutting plate test mold with a length of 300 mm, a width of 300 mm, and a height of 50 mm; the second mold (2) is a rutting plate test mold with a length of 300 mm, a width of 300 mm, and a height of 100 mm. The thickness of the asphalt mixture spread on the base plate is 20 mm to 25 mm.

3. The method for detecting fatigue performance of asphalt pavement according to claim 1, characterized in that: The composite beam is 300 mm long, 100 mm wide and 75 mm thick, and contains a 50 mm thick cement-stabilized crushed stone layer (3) and a 25 mm thick asphalt surface layer (5).

4. The method for detecting fatigue performance of asphalt pavement according to claim 1, characterized in that: The application range of the barrier agent (4) is set in several types of arrangements. The test composite panels with different application ranges of the barrier agent (4) are divided into three groups of samples, namely: Group A: Sample A201 has an interlayer barrier of 0%, sample A202 has an interlayer barrier of 25%, sample A203 has an interlayer barrier of 50%, sample A204 has an interlayer barrier of 75%, and sample A205 has an interlayer barrier of 100%; Group B: The centroid distance between the damaged parts of the layers of sample B201 is 37.5mm; the centroid distance between the damaged parts of the layers of sample B202 is 46.9mm; the centroid distance between the damaged parts of the layers of sample B203 is 56.25; the centroid distance between the damaged parts of the layers of sample B204 is 65.63mm; the centroid distance between the damaged parts of the layers of sample B205 is 75mm; Group C: The interlayer friction coefficient of sample C201 is 0.4, the interlayer friction coefficient of sample C202 is 0.5, the interlayer friction coefficient of sample C203 is 0.6, the interlayer friction coefficient of sample C204 is 0.7, and the interlayer friction coefficient of sample C205 is 0.

8.

5. The method for detecting fatigue performance of asphalt pavement according to claim 1, characterized in that: The barrier agent (4) is a high temperature resistant smooth paint.

6. The method for detecting fatigue performance of asphalt pavement according to claim 1, characterized in that: The binder (6) is emulsified asphalt.

7. The method for detecting fatigue performance of asphalt pavement according to claim 1, characterized in that: Step 5) The medium load is applied by setting two support points symmetrically on the left and right sides of the bottom of the composite beam and applying pressure to the midpoint of the top surface of the composite beam.

Citation Information

Patent Citations

  • Method for evaluating pavement interlayer adhesion effect based on fatigue test of composite beam

    CN108469389A

  • Preparation method of test piece for testing post-service mechanical properties of material

    CN111795878A

  • On-site simulation method based on nondestructive test of pavement interlayer bonding strength

    CN113640215A

  • Method for evaluating performance of carbon fiber reinforced resin-based composite material based on ultrasonic detection

    CN117805234A

  • Testing method for monitoring layering defect expansion process of composite material in fatigue environment

    CN118817505A

Cited By

  • Road property adaptive topology awareness and application system and method

    CN120279746A

  • Fatigue performance analysis method for asphalt mixture of asphalt pavement

    CN121068391A

  • A method for analyzing fatigue performance of asphalt pavement asphalt mixture

    CN121068391B